Case Report: Anastrozole as a monotherapy for pre-pubertal children with non-classic congenital adrenal hyperplasia - Liu, Sandy C.; Suresh, Malavika; Jaber, Mutaz; Mercado Munoz, Yesica; Sarafoglou, Kyriakie (Frontiers in Endocrinology, 2023)
Most children with non-classic congenital adrenal hyperplasia (NC-CAH) due to 21-hydroxylase deficiency are asymptomatic and do not require cortisol replacement therapy unless they develop symptoms of hyperandrogenemia. Current practice is to treat symptomatic children with hydrocortisone aimed at suppressing excess adrenal androgen production irrespective of the child’s level of endogenous cortisol production. Once on hydrocortisone therapy, even children with normal cortisol production require stress dosing. Some children with NC-CAH may present with premature pubarche, growth acceleration and advanced bone age, but with no signs of genital virilization and normal endogenous cortisol production. In these cases, an alternative therapy to hydrocortisone treatment that does not impact the hypothalamic-pituitary-adrenal axis, but targets increased estrogen production and its effects on bone maturation, could be considered. Aromatase inhibitors (AI), which block the aromatization of androgen to estrogen have been used off-label in males with short stature to delay bone maturation and as an adjunct therapy in children with classic CAH. The use of AI as a monotherapy for children with NC-CAH has never been reported. We present three pre-pubertal female children with a diagnosis of NC-CAH treated with anastrozole monotherapy after presenting with advanced bone age, early pubarche, no signs of genital virilization and normal peak cortisol in response to ACTH stimulation testing. Bone age z-scores normalized and all three reached or exceeded their target heights. Monotherapy with anastrozole can be an effective alternative in slowing down bone maturation and improving height outcomes in children with NC-CAH and normal adrenal cortisol production.